English and French-major students’ suggestions on extracurricular activities for English learning: A case in the Mekong Delta - Mai, Le Xuan; Thao, Le Thanh (Nurture, 2023)
Purpose: Extracurricular activities (ECA) are encouraged by education stakeholders in Vietnam to contribute to improving the English ability of Vietnamese people. At universities, ECA is organized quite a lot, but there is a lack of consultation from students. Therefore, this study aimed to investigate the English and French majors’ preferred ECA for English learning. Design/Methodology/Approach: This study involved 151 students from two groups of students majoring in foreign languages, English and French. A questionnaire was used to gather the students’ perspectives on how to implement ECA for English language learning. Findings: The results showed that most students favored experiential travel to places where English is used frequently to help them improve their oral skills. However, the students were not interested in multi-day activities, mandatory-participation policies, individual activities, or online-organized events. Conclusion: The research results suggest ideas for organizing ECA for English learning for students majoring in French and English. Practical implications: The research team proposed a specific tourism simulation activity in this paper based on the results, which can be a useable source for further ECA for English learning organized in the context of higher education institutions in Vietnam and elsewhere. Limitations: This study focused on students majoring in foreign languages, so its applicability to non-foreign language-major students is limited. Further studies in this field should focus on gathering perspectives from non-foreign-language majors. Contribution to literature: The literature on ECA for English learning has not yet received adequate attention. Therefore, this study contributes to the relevant literature and suggests significant topics for future research.